ANALISIS KEBIJAKAN PENDIDIKAN ISLAM DI PROBOLINGGO DALAM PENGUATAN AKSESIBILITAS DAN PENINGKATAN KUALITAS BELAJAR: Analysis Of Islamic Education Policy In Probolinggo In Strengthening Accessibility And Improving The Quality Of Learning - Nadifah (Piwulang: Jurnal Pendidikan Agama Islam, 2025)
This study aims to examine the implementation of Islamic education policies in Probolinggo Regency, focusing on enhancing accessibility and improving the quality of learning. The background of this research highlights the importance of Islamic education in shaping the cultural identity of the community and the challenges faced in improving education quality in the region. This research employs a qualitative approach with a descriptive-analytical method, gathering data through in-depth interviews, field observations, and document studies related to the Islamic education policies in Probolinggo. The results of the study show that local government policies, such as expanding educational infrastructure, integrating Islamic education into the general education system, and utilizing digital technology, have improved educational access in remote areas. However, challenges such as digital infrastructure gaps and the quality of human resources still need to be addressed. The study concludes that continuous evaluation and policy adjustments are required for the effectiveness of Islamic education policies in adapting to changing times. The implications of this research emphasize the importance of strengthening digital infrastructure, continuous training for teachers, and closer collaboration between the government and non-governmental educational institutions to ensure sustainable and relevant Islamic education quality.